The holy city : an oratorio - GAUL, A.R. (G. Schirmer. Inc.)
No shadows yonder, My soul is athirst for God, At eventide it shall be light,They that sow in tears,Eye hath not seen, For thee O dear dear sountry, Thine is the kingdom, Adoration,A New heaven and a new Earth, Let the heavens rejoice,